Dinamika Hukum Akad Nikah Via Teleconference Di Indonesia - Muhammad Alwi Al-Maliki; Asep Saepudin Jahar (JURNAL INDO-ISLAMIKA, 2020)
This research aims to review the dynamics of the teleconference marriage contract law in Indonesia and to analyze the legal provisions from three perspectives: juridical, philosophical, and sociological. This research is library research with a descriptive-analytical method. The primary legal data is in the form of several fiqh opinions and fatwas of the ulama regarding the legal provisions of the marriage contract via teleconference. The results of this study indicate that there are differences of opinion among scholars based on different methods of understanding the al-Quran and hadith texts about marriage and the development of science and technology. In Indonesia, when examined from a juridical-philosophical aspect, the practice of the marriage contract via teleconference can be carried out because the facilities are complete and the requirements can be fulfilled. However, when examined from a sociological aspect, the paradigm of the majority of Muslim communities regarding the sacredness of marriage is still strong so that the permissibility of the practice of the marriage contract is still difficult to accept and apply among them.